Влияние эффективности исходных материалов на показатели надежности термоэлектрических охлаждающих устройств. Часть 2: Двухкаскадные ТЭУ - Зайков, В.П.; Мещеряков, В.И.; Журавлев, Ю.И. (Технология и конструирование в электронной аппаратуре, 2015)
В продолжение исследований однокаскадных термоэлектрических устройств (ТЭУ) рассмотрено влияние термоэлектрической эффективности исходных материалов модулей на показатели надежности двухкаскадных ТЭУ. Показано, что с ее ростом уменьшается интенсивность отказов и увеличивается вероятность безотказной работы двухкаскадного ТЭУ для различных значений перепада температуры (от 60 до 90 К) и условий функционирования. У продовження досліджень однокаскадних термоелектричних пристроїв (ТЕП) розглянуто вплив термоелектричної ефективності вихідних матеріалів модулей на показники надійності двокаскадних ТЕП. Показано, що з її ростом зменшується інтенсивність відмов і збільшується ймовірність безвідмовної роботи двокаскадного ТЕП для різних значень перепаду температури (від 60 до 90 К) і умов функціонування. Extended operation temperature range of elements and electronic equipment components using thermoelectric devices necessitates the use of cascade thermoelectric cooling devices. One of the best ways to improve the reliability of thermoelectric coolers is to improve the efficiency of thermoelectric materials. The article presents the research results on the influence of thermoelectric efficiency of initial materials on the failure rate and probability of failure of the two-stage thermoelectric cooler within temperature range of 60 to 90 K for maximum cooling operation modes and low failure rate. The results have shown that with the increase in the thermoelectric efficiency of the material thermocouples the maximum temperature difference in cascades increases, the working current and the ratio of the elements number in the adjoining cascades decreases (depending on the current mode in cascades of thermoelectric device from the mode of the maximum cooling capacity up to the minimum failure rate), the cooling coefficient increases, the failure rate reduces and the probability of failure-free operation of two-stage thermoelectric cooler increases. Thus, it is shown that the increase in the thermoelectric efficiency of initial materials can significantly reduce the failure rate and increase the probability of failure-free operation of the two-stage thermoelectric devices depending on temperature difference and the current mode of operation.